Contemporary Trends in the Studies of Graduate Students in Physical Geography at the University of Basra - Nouri Ali , Assist .Prof. Dr. Nadia (Basra studies journal, 2026)
The scientific importance of any study depends on its originality, innovation, development, and the extent of its real contribution to scientific knowledge. Hence, the importance of natural studies in understanding the world surrounding human life and the extent of their significant impact on human activities and life stems from this. From this standpoint, the study aimed to identify the volume of output of postgraduate students in the geography departments at the University of Basra, to understand its trends and methodological changes during the study period (1985-2022), to analyze it quantitatively and qualitatively, to identify the three time periods of this output, in order to reveal the most quantitatively and qualitatively outstanding outputs, and then to determine their methodologies and trends. This was achieved through a comprehensive survey and inventory of scientific theses and university dissertations according to the main fields of physical geography. The research relied on the descriptive analytical method to identify, describe, and explain the quantitative and qualitative changes, as well as the historical method One of the most important findings of the research is the diversity of trends in the study of the main fields of physical geography at the University of Basra and their quantitative and qualitative development during three time periods through what the departments of geography approved in terms of geographical theses (Master’s and PhD) amounting to (117) geographical studies during the period (1985-2022 AD), issued within four fields in physical geography, produced by more than (108) geographical researchers at the University of Basra .